A Clinical Study to Evaluate the Effect of Gokshuru Kwatha in the Management of Mutrakrichra w.s.r. to Urinary Tract Infection (AYUSHDHARA, 2024)
Urinary tract infections are the most common infections, after respiratory tract infections. 40-50% females suffer from UTI at least once in their life time. Although, modern medical system has many drugs to manage UTI but there are limitations. The use of antibiotics have side effects. Chances of re-infection and relapse even after long term therapy. Increasing incidence of resistance and high cost of therapy are common problems. In Ayurvedic texts, many herbal drugs have been mentioned for the treatment of Mutrakrichra. So, this study was planned to evaluate the safety and efficacy of herbal drug in the management of Mutrakrichra w.s.r. U.T.I. The goal of this study was to find an effective, well accepted drug with minimal or no complications and no side effects. A total number of 60 patients, who were diagnosed with Mutrakrichra w.s.r. to Urinary Tract Infection were randomly divided into two groups – Group I and Group II- consisting of 30 patients each. The trial drug i.e., Gokshuru Kwatha was given in the dose of 40ml twice a day to 30 patients of Group I, whereas, the standard drug i.e., Tablet Norfloxacin 400mg twice a day was given to 30 patients of Group II, for a duration of 1 week. The effect of therapy was assessed on the basis of subjective parameters, before and after the completion of the trial and the data obtained during the trial was then statistically analyzed.